SIMULATING CYBERATTACKS IN A VIRTUAL ENVIRONMENT: A CASE STUDY IN THREAT DETECTION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
In this study, we present how we simulated cyberattacks in a controlled virtual environment to assess the security and detection abilities of a Windows 7 system. Using common penetration testing tools, we recreated realistic scenarios including port scanning, brute-force login attempts, password cracking from NTLM hashes, and phishing with cloned websites. Our findings revealed that outdated systems, when left unpatched and poorly monitored, are especially vulnerable, thereby underlining the need for regular updates, strong password practices, and real-time monitoring to reduce risk, while providing insights into how such environments can be tested and strengthened against different cyberthreats.
Keywords: Cybersecurity; Network security; Penetration testing; Virtual simulation; Ethical hacking